A histone acetylome-wide association study of Alzheimer's disease identifies disease-associated H3K27ac differences in the entorhinal cortex. (November 2018) - Marzi, Sarah; Leung, Szi; Ribarska, Teodora; Hannon, Eilis; Smith, Adam; Pishva, Ehsan; Poschmann, Jeremie; Moore, Karen; Troakes, Claire; Al-Sarraj, Safa; Beck, Stephan; Newman, Stuart; et al.
Abstract We quantified genome-wide patterns of lysine H3K27 acetylation (H3K27ac) in entorhinal cortex samples from Alzheimer's disease (AD) cases and matched controls using chromatin immunoprecipitation and highly parallel sequencing. We observed widespread acetylomic variation associated with AD neuropathology, identifying 4, 162 differential peaks (false discovery rate < 0.05) between AD cases and controls. Differentially acetylated peaks were enriched in disease-related biological pathways and included regions annotated to genes involved in the progression of amyloid-β and tau pathology (for example, APP, PSEN1, PSEN2, andMAPT ), as well as regions containing variants associated with sporadic late-onset AD. Partitioned heritability analysis highlighted a highly significant enrichment of AD risk variants in entorhinal cortex H3K27ac peak regions. AD-associated variable H3K27ac was associated with transcriptional variation at proximal genes includingCR1, GPR22, KMO, PIM3, PSEN1, andRGCC . In addition to identifying molecular pathways associated with AD neuropathology, we present a framework for genome-wide studies of histone modifications in complex disease. Widespread differences in H3K27ac, a key histone modification, are associated with Alzheimer's disease. H3K27ac differences were enriched in genomic regions containing loci involved in the progression of Aβ and tau pathology.